EFFECTS OF THE CUSTOM UNION OF BELARUS, KAZAKHSTAN, AND RUSSIA ON DEVELOPMENT OF KAZAKHSTAN ECONOMY (Journal of Economic Research & Business Administration, 2015)
The Custom Union of Belarus, Kazakhstan, and Russia is huge step forward in integration process of post soviet union countries. The difference of Custom Union from previous agreements is the formation of supranational body - the Customs Union Commission that will decide on CommonExternal Tariffs – CET and other trade related issues. The current paper examines what would be effect of the Custom Union of Belarus, Kazakhstan, and Russia on Economy of Kazakhstan and especially on domestic producers and export opportunities.